Milling and rheological properties of high amylose wheat. (November 2021) - De Arcangelis, Elisa; Trivisonno, Maria Carmela; Angelicola, Martina; Quiquero, Michela; Di Nardo, Valentina; Falasca, Luisa; Sestili, Francesco; Messia, Maria Cristina; Marconi, Emanuele
Abstract: The technological quality of a high amylose bread wheat variety (amylose/amylopectin 1:0.7) was explored performing different milling protocols, with subsequent evaluation of the chemical composition and rheological properties of the milling fractions and recombined flours. High amylose wheat yielded a lower amount of flour (<50%) and less refined products compared to control line. Grain debranning improved flour yields, releasing more refined reduction products. The milling of high amylose wheat with a hard-wheat diagram enhanced flour yield and refining rate of products, also giving a semolina type flour that can be employed e.g. for the production of pasta and couscous. The high amylose flours are characterized by relevant levels of resistant starch (27% of total starch on average) that make them suitable for the production of functional foods in agreement with the EU Regulation 432/2012. In addition, from the experimental results, it was put in evidence that official protocols for rheological analysis of flours (gluten index, alveograph and falling number) should be adapted for high amylose wheat samples, due to the impact that the different starch composition has on dough properties, specifically on water absorption and viscosity. Overall, rheological features of high amylose wheat flours exhibited higher water absorption, stability, and altered starch pasting properties. Graphical abstract: Image 1 Highlights: Debranning enhanced milling performance of high amylose wheat. High amylose flours showed high levels of resistant starch (27% of total starch). High amylose starch properties influenced applicability of conventional rheological analysis.